Measuring plant cysteine oxidase interactions with substrates using intrinsic tryptophan fluorescence - Dona M. Gunawardana; Daisy A. Southern; Emily Flashman (Scientific Reports)
Abstract Plant Cysteine Oxidases (PCOs) are oxygen-sensing enyzmes that catalyse oxidation of cysteinyl residues at the N-termini of target proteins, triggering their degradation via the N-degron pathway. PCO oxygen sensitivity means that in low oxygen conditions (hypoxia), their activity reduces and target proteins are stabilised. PCO substrates include Group VII Ethylene Response Factors (ERFVIIs) involved in adaptive responses to the acute hypoxia experienced upon plant submergence, as well as Little Zipper 2 (ZPR2) and Vernalisation 2 (VRN2) which are involved in developmental processes in hypoxic niches. The PCOs are potential targets for improving submergence tolerance through enzyme engineering or chemical treatment. To achieve this, a detailed understanding of their biological function is required. Here, we report development of an assay that exploits the intrinsic fluorescence of Arabidopsis thaliana PCO tryptophan residues. By using Ni(II)-substitued enzymes and preparing the assay under anaerobic conditions, tryptophan fluorescence quenching is observed on enzyme:substrate complex formation, allowing quantification of binding affinities. Our assay revealed that, broadly, AtPCO4 and AtPCO5 have stronger interactions with ERFVII substrates than ZPR2 and VRN2, suggesting ERFVIIs are primary targets of these enzymes. It also revealed a positive cooperative binding effect for interactions between AtPCOs4/5 and ERFVIIs and ZPR2. The assay is experimentally straightforward and can be used to further interogate PCO interactions with substrates.